Experimental evaluation and hydrocarbon significance of natural fractures in Shunbei ultra-deep carbonate reservoir, Tarim Basin - Yingtao LI; Zhixing RU; Shang DENG; Huixi LIN; Jun HAN; Jibiao ZHANG; Cheng HUANG (Shiyou shiyan dizhi, 2023)
There are abundant hydrocarbon resources in the strike-slip fault-controlled ultra-deep carbonate reservoirs in the Shunbei area, Tarim Basin. Large strike-slip faults and natural fractures are the main storage space and flow channel of hydrocarbon resources. It is of great significance to study the natural fracture development characteristics in such reservoirs. 39 limestone samples and 7 dolomite samples from 5 wells in Shunbei area are taken as research objects. Through the analysis of thin section of lithofacies, fine description of natural fractures and brittleness test evaluation of core samples, the main controlling factors and influence laws of natural fracture development in Shunbei reservoir are studied. It is found that the reservoir lithology of Middle and Lower Ordovician Yingshan Formation and Yijianfang Formation in Shunbei area is dolomite and limestone, and the lithofacies include grainstone, wackestone, packstone, boundstone, muddy limestone, silicified limestone, silty-fine crystal dolomite and medium-coarse crystal dolomite. In limestone samples, muddy limestone has the highest brittleness index and natural fracture development density, while boundstone has the lowest brittleness index and natural fracture development density. In dolomite samples, the brittleness index of medium-coarse crystalline dolomite is higher than that of silty-fine crystal dolomite, and the coarser the grains are, the more developed the natural fractures are. There is a positive correlation between the natural fracture development density and the brittleness index of rock samples. The porosity, permeability and brittleness index of dolomite are higher than those of limestone. Under the same brittleness index, the fracture development ability of limestone is stronger. Therefore, the highly brittle section of limestone stratum is more likely to be the geological sweet spot in Shunbei area.